Hepatoprotective Activity of Chenopodium Album Linn. Against Alcohol Induced Liver Damage - Vijay Nigam; Padmaa M Paarakh (International Journal of Phytomedicine, 2011)
Dried aerial parts of Chenopodium album Linn. (Chenopodiaceae) are used in variety of diseases in traditional Indian system of medicine including hepatic ailments. The aim of present study was to validate hepatoprotective activity of aerial parts of Chenopodium album Linn using alcohol as chronic hepatitis model. Alcoholic [ALCA] and aqueous [ AQCA] extracts of the aerial parts of Chenopodium album at the doses of 200 and 400 mg/Kg were evaluated for hepatoprotective activity against alcohol induced hepatotoxicity using biochemical markers and by histopathological method. The aqueous extract at a dose of 400 mg/kg was found to be more potent when compared to Silymarin. ALCA and AQCA [200 & 400 mg/Kg] showed significant hepatoprotective activity against alcohol induced hepatotoxicity as evident by restoration of serum transaminases, alkaline phosphatase and bilirubin content. Histopathology of the liver tissue further confirmed the reversal of damage induced by hepatotoxin.Present study showed that the alcoholic and aqueous extracts of Chenopodium album significantly restore physiological integrity of hepatocytes. Aqueous and alcoholic extract did not show any sign of toxicity up to oral dose of 5 g/Kg in mice.